Sex differences in the clinical presentation and therapy of multiple sclerosis - Nacka-Aleksić Mirjana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Multiple sclerosis (MS) is more prevalent in women than in men, with the female to male ratio in the prevalence of MS constantly increasing. Besides, sex appears to affect the development, progression, clinical manifestation and therapy response in MS. These sex differences, most likely, emerge from the genetic, epigenetic and hormonal differences between the sexes, differences in environmental exposure and/or susceptibility to certain factors, as well as from the biological differences in the female and male immune and nervous system. Therefore, sex differences in all of these aspects need to be taken into consideration when designing and interpreting research findings related to MS, and particularly in development of new therapeutic strategies and designing of clinical drug trials. Understanding the mechanisms underlying sex differences in the pathogenesis and/or therapy response in MS could also narrow the gap in our knowledge of the pathogenesis/therapy of a broad spectrum of other autoimmune diseases that are characterized by sexual dimorphism in the prevalence and/or clinical presentation.